Leukocyte Adhesion: A Suitable Target for Anti-Inflammatory Drugs - Mrowietz, Ulrich; Boehncke, Wolf-Henning (Current Pharmaceutical Design, 2006)
Inflammatory responses in all tissue compartments require the emigration of leukocytes from the microvasculature through endothelial cells into the respective microenvironment. Adhesion to endothelial cells is the most crucial step in order to facilitate selective and effective capture of leukocytes. The sequence of adhesions events, e.g. rolling, tethering, and firm adhesion are tightly regulated by a variety of molecules expressed by endothelial cells and leukocytes either constitutively or after induction by mainly inflammatory mediators. In diseases with a prominent inflammatory response such as psoriasis, rheumatoid arthritis, or Crohn’s disease, interference with leukocyte adhesion and/or emigration may be of substantial clinical effect. A number of therapeutic approaches by using monoclonal antibodies, designed molecules, and other modulators of adhesion molecule expression have been investigated in clinical trials. This review aims to give an overview about the current knowledge of targeting adhesion molecules as a therapeutic strategy to treat inflammatory diseases.
Keywords: Glucocorticoids